2016
DOI: 10.1016/j.memsci.2016.05.026
|View full text |Cite
|
Sign up to set email alerts
|

A review of the water barrier properties of polymer/clay and polymer/graphene nanocomposites

Abstract: This paper reviews the literature on moisture barrier properties of polymer/clay and polymer/graphene-based nanocomposites. The various models proposed to predict the effects of nanofillers in reducing water vapour permeability through polymers are outlined. These models are based on a range of different factors such as; tortuosity, geometry, platelet stacking, orientation, polymer chain confinement and plasticization.Published experimental studies of water vapour permeability in both polymer/clay and polymer/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
145
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 291 publications
(157 citation statements)
references
References 118 publications
(244 reference statements)
3
145
0
9
Order By: Relevance
“…This further confirmed the formation of hydrogen bonding between GO nanosheets and PVA matrix, which reduced the polymer chain mobility. This could be also lead to the rigidification of polymer chains near the GO sheets [15]. Similar trends were also observed by incorporating a small amount of GO into PVA matrix [45,48].…”
Section: Characterizationssupporting
confidence: 66%
“…This further confirmed the formation of hydrogen bonding between GO nanosheets and PVA matrix, which reduced the polymer chain mobility. This could be also lead to the rigidification of polymer chains near the GO sheets [15]. Similar trends were also observed by incorporating a small amount of GO into PVA matrix [45,48].…”
Section: Characterizationssupporting
confidence: 66%
“…The lower interaction among this filler and the non‐polar PP did not contribute to a good dispersion of the filler in the matrix, forming agglomerates and allowing more free movement of the oxygen molecules through the polymer–filler interface . It has been stated that permeability should decrease as crystallinity increases . In this work we found that the crystallinity of all nanocomposites was reduced with respect to the polymer matrix.…”
Section: Resultsmentioning
confidence: 99%
“…Although the interest in polymer/layered silicate nano composites has ebbed somewhat recently, relatively intensive work is going on in the field and a large number of papers are published [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. The decrease of interest is caused by the fact that the nano hype has not been justified and a breakthrough has not occurred in the application of such composites.…”
Section: Introductionmentioning
confidence: 99%